Expert Identification of an Unknown Hero of the Great Patriotic War - A. M. Zinin (Теория и практика судебной экспертизы)
On the 80th anniversary of the Great Victory, veterans of the Russian Federal Centre of Forensic Science recall the unique examinations of objects related to both the tragic and heroic events of those fiery years. In this essay, the author pays attention to the identification of the commander captured by Max. Alpert in the famous photograph which provided the basis for the sculpture “Battalion Commander”.